Internationalization of Higher Education: International Vector of the University Development Strategy - A. V. Akulshina; L. A. Zavialova (Moscow Polytechnic University, 2018)
The article focuses on internationalization of higher education. It analyzes the European experience of implementing internationalization strategies on  the examples of Aston University (United Kingdom) and Sapienza University  of Rome (Italy). The authors present the results of the research on defining  the level of internationalization conducted at Russian higher education  institutions under Erasmus+ project "Development of approaches to  harmonization of comprehensive internationalization strategies in higher  education, research and innovation at EU and partner countries (HARMONY)". The project partnership is comprised of 14 higher education institutions of  different types (classical universities, institutions of applied sciences) from 9  countries of the world, namely Spain, United Kingdom, Germany, Portugal,  Italy, Greece, Russia, Belarus, and Armenia. In Russia the questionnaires  were sent to 119 universities located in four Russian federal districts  including the Central, North-Western, Volga and Southern federal districts.  The survey was based on data of 2015-2016 academic year. Finally, the  article analyzes the cooperation between Russia and European Union in the  framework of Erasmus+ programme and the role that the programme plays  in internationalization of higher education.